Application of Nannochloris sp. for Landfill Leachate Biotreatment and Lipids Production - Ildefonso Baldiris-Navarro; Jorge Sanchez; Martha Torres Virviescas; Alvaro Realpe-Jimenez; Juan Fajardo-Cuadro (Universitas Gadjah Mada, 2023)
The sparse treatment of highly toxic leachates produced in landfills due to the excessive generation of urban solid waste is a common problem worldwide. For this reason, this research aims to show the convenience of the use of algal biotechnology in leachate bioremediation processes. Nannochloris sp. species was used in this research. It was isolated and cultured for bioassays. The leachate was diluted to 5 and 10% in the microalgae cultures during a period of 8 d in which the growth of the species. Then removal of nutrients (phosphate and nitrate) and the production of lipids by the microalgae were measured. Nannochloris sp. removed more than 70% of the phosphates and 60% of the nitrates from samples. This result shows the benefits of using these microalgae to treat landfill leachate at low cost and also with the potential to obtain bio-lipids that may be useful for biodiesel production.